The influence of plyometric training on the freestyle tumble turn - Cossor, J. M.; Blanksby, B. A.; Elliott, B. C. (Journal of Science and Medicine in Sport, 1999)
This study examined the effects of a plyometric training program on freestyle tumble turns. Thirty-eight age group swimmers were assigned to a control group which swam 1.5 hours, three times per week for 20 weeks; or an experimental group which supplemented 1.25 hours of swimming with 15 minutes of plyometrics for the same time frame. The same coach conducted all swimming and plyometric sessions to ensure uniformity. Swimming performance was assessed from 50 m time. Freestyle turning performance was measured by 2.5 m round trip time (RTT), 5 m RTT, wall contact time and selected kinematic and kinetic variables associated with the turn. A Plyopower system was also used to test jump height and velocity. Repeated measures, multivariate analysis of variance showed no significant differences between the groups (pre-, mid- and post-intervention) over the period of the study for any swimming, kinetic or plyopower measures. Thus, equal benefits were derived from normal practice time in the water or land based plyometric exercises